A Covalent Triazine‐Based Framework Consisting of Donor–Acceptor Dyads for Visible‐Light‐Driven Photocatalytic CO2 Reduction. Issue 19 (3rd September 2019) - Zhong, Hong; Hong, Zixiao; Yang, Can; Li, Liuyi; Xu, Yangsen; Wang, Xinchen; Wang, Ruihu
Abstract: Photocatalytic conversion of CO2 into value‐added chemical fuels is a promising approach to address the depletion of fossil energy and environment‐related concerns. Tailor‐making the electronic properties and band structures of photocatalysts is pivotal to improve their efficiency and selectivity in photocatalytic CO2 reduction. Herein, a covalent triazine‐based framework was developed containing electron‐donor triphenylamine and electron‐acceptor triazine components (DA‐CTF). The engineered π‐conjugated electron donor–acceptor dyads in DA‐CTF not only optimized the optical bandgap but also contributed to visible‐light harvesting and migration of photoexcited charge carriers. The activity of photocatalytic CO2 reduction under visible light was significantly improved compared with that of traditional g‐C3 N4 and reported covalent triazine‐based frameworks. This study provides molecular‐level insights into the mechanism of photocatalytic CO2 reduction. Abstract : Triple threat ! A covalent triazine‐based framework consisting of triphenylamine and triazine (DA‐CTF) displays high catalytic activity, selectivity, and stability in visible‐light‐driven CO2 reduction. The superior photocatalytic performance is mainly attributed to the unique structure of DA‐CTF. The π‐conjugated electron donor–acceptor dyads contribute to visible‐light harvesting and migration of photoexcited charge carriers, whereas the porosities are favorable for CO2 capture and the accommodation of electron mediators.